The impact of solvent characteristics on performance and process stability of printed carbon resistive materials - Eifion Jewell (Journal of Coatings Technology and Research, 2016)
Carbon conductive pastes deposited by screen printing are used in many commercial applications including sensors, PCB, batteries, and PV, and as such represent an important value-added coating. An experimental investigation was carried out into the role of the solvent on the drying characteristics, conductivity, and process consistency in screen printed carbon pastes. Four materials with solvent boiling points between 166 and 219°C were deposited at film thickness between 6 and 16 μm, and the sheet resistance and film thickness were measured after successive passes through an industrial dryer operating with an air temperature of 155°C. Sheet resistances of 14 Ω/sq. were obtained with the thicker films while thinner films produced a sheet resistance of 46 Ω/sq. Thinner films achieved a stable resistivity within a 2.5-min residence time, while the thicker films required a residence time in excess of 12.5 min to achieve a stable resistivity. As well as prolonging drying times, the higher boiling point increased the resistivity of the cured film. It is postulated that the lower resistance of the faster drying materials is a result of film stressing increasing inter particle contact. Process models indicate that multiple thin layers are a more efficient means of manufacture for the process parameters examined.